Cechy użytkowników języków obcych sprzyjające interkomunikacji (komunikacji w językach pokrewnych) - Grabowska, Anna (Neofilolog, 2017)
The article reflects on individual differences of foreign language users from the standpoint of polylingual communication in two related languages (intercommunication), on the basis of the work of Paolo Balboni on intercomprehension, intercommunication and useful approaches to foreign language learning. The author attempts to elaborate a list of individual characteristics which facilitate intercommunication (a conversation in which the participants speak different, but related languages). The discussion relates to features presented by selected authors in the field of foreign language teaching, the European documents on language education (CEFR and FREPA) and to psycholinguistics. The final part describes the characteristics which favour intercommunication.